Thomas Radcliffe Comber (1837–1902), his contribution to the diatoms recorded in the Catalogue of African Plants Collected by Dr. Friedrich Welwitsch in 1853–1861 (1898–1901) with notes on nomenclatural issues and biogeographical implications - Williams, David M.; Blanco, Saúl (Phytotaxa, 2020)
This paper is an examination of Thomas Comber’s diatom contribution to the Catalogue of African Plants Collected by Dr. Friedrich Welwitsch in 1853-1861. It includes notes on the new taxa described, deals with a few nomenclatural issues and very briefly considers the biogeographical implications of museum collections.